2018
DOI: 10.1016/j.antiviral.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Host functions used by hepatitis B virus to complete its life cycle: Implications for developing host-targeting agents to treat chronic hepatitis B

Abstract: Similar to other mammalian viruses, the life cycle of hepatitis B virus (HBV) is heavily dependent upon and regulated by cellular (host) functions. These cellular functions can be generally placed in to two categories: (a) intrinsic host restriction factors and innate defenses, which must be evaded or repressed by the virus; and (b) gene products that provide functions necessary for the virus to complete its life cycle. Some of these functions may apply to all viruses, but some may be specific to HBV. In certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 200 publications
(217 reference statements)
0
59
0
Order By: Relevance
“…Despite the dispensable role of precore in the HBV replication cycle, the observed high viremia and low immune system activation in HBeAg ϩ chronic hepatitis B patients directs attention to the role of HBeAg and/or p22 in relation to the regulation of host defense and virus persistence (7,9,20,26). Furthermore, it has been reported that HBeAg Ϫ patients respond better to standard IFN-␣ therapy than do HBeAg ϩ patients (47-51), suggesting that either HBeAg or its precursor, p22, might have an inhibitory effect that prevents the IFN therapy from working to its full potential in HBeAg-positive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the dispensable role of precore in the HBV replication cycle, the observed high viremia and low immune system activation in HBeAg ϩ chronic hepatitis B patients directs attention to the role of HBeAg and/or p22 in relation to the regulation of host defense and virus persistence (7,9,20,26). Furthermore, it has been reported that HBeAg Ϫ patients respond better to standard IFN-␣ therapy than do HBeAg ϩ patients (47-51), suggesting that either HBeAg or its precursor, p22, might have an inhibitory effect that prevents the IFN therapy from working to its full potential in HBeAg-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upon HBV infection, the virion containing the relaxed circular DNA (rcDNA) genome is transported into the cell nucleus and converted to an episomal cccDNA, which assembles into a minichromosome and serves as a transcription template for all the viral mRNAs (8,9). Four groups of viral RNA are transcribed from cccDNA, namely, the 3.5-kb precore mRNA that encodes the precore protein, another 3.5-kb pregenomic RNA (pgRNA) that encodes the core and the polymerase, a 2.4-kb mRNA for the large (L) envelope protein, a 2.1-kb mRNA for the middle (M) and major surface (S) proteins, and a 0.7-kb mRNA for the X protein (1,2).…”
mentioning
confidence: 99%
“…HBV entry can be mediated by heparan sulphate proteoglycan (HSPG) such as Glypican-5 (GPC5), sodium taurocholate co-transporting polypeptide (NTCP). [11][12][13][14] HBV transcription is also regulated by liver-enriched transcriptional factors such as hepatocyte nuclear factors (HNF) including HNF1, HNF3 and HNF4, CCAAT/enhancer-binding protein (C/EBP), and nuclear hormone receptors such as RXRa and PPARa. 11,[15][16][17][18] The initial step of HBV infection involves binding of the virus to a receptor on the target cell surface and initiating viral entry.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the side effects of interferon-alpha or drug resistance for NAs (Zoulim and Locarnini, 2009), the current therapeutic efficacy is limited. Therefore, developing new drugs that directly target either virus or host factors for an efficient CHB treatment is viral and urgent (Mitra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%